PERTUMBUHAN PADI HITAM VARIETAS WOJALAKA YANG DIBUDIDAYAKAN DENGAN SISTEM TANAM BANJAR - Ramadhani Kurnia Adhi (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
This research is aimed to study growth adaptation of Wojalaka black rice variety which is cultivated with The Banjarese system cultivation and its problem during planting period. A descriptive exploratory research was conducted in rainfed rice field in Binuang Village, Binuang District, Tapin Regency, South Kalimantan Province on November 2016 to May 2017. Land preparation was done with Tepulikampar technology and the seedbed was done in two stages, i.e. dry seedbed and continued with wet nursery. Observations were made on plant height, plant age, number of productive tillers, panicle length, number of seeds per panicle, weight per panicle, weight of 1000 seeds, total weight and problems during plant growth including pests, diseases and environmental conditions. The results showed that Wojalaka black rice variety were 125 cm high and the plant age was 176 days or longer than the normal age of 127 days. Number of productive tillers is relatively small as many as 12 tillers. The yield potential is almost equal to the potential yield in the area of origin. The Banjarese planting system is less suitable to be applied to the Wojalaka black rice variety because it causes the longer period of harvest and the decrease of the harvest. The attacks of rice ear bugs and birds and diseases caused by fungus Ustilaginoidea virens also cause the decline of crop yields.Keywords: Black rice, Growth, Wojalaka, Banjarese system cultivation